Case Study: Satisfying Skills Needed of Engineering Graduates through a Course on Innovation - Raj L Desai; M. David Papendick (Bulletin of Electrical Engineering and Informatics, 2012)
The purpose of this paper is to report a case study that develops the skills necessary to compete in a global economy by going through the cycle of product development. The best way to equip students with the skills to survive and thrive in a global economy is to teach innovation. Students can develop their skills by working in small teams to generate, evaluate, develop, and market their innovation.